Be brave a multi-sensory storybook kit for Filipino parents to use as a tool to build a confidence and resilience in their children of ages 6 to 8 who are afraid of being on their own - Yu, Charmaine Regina S.; Reyes, Mitzi Marie Aguilar (Quezon City College of Fine Arts, University of the Philippines Diliman, 2019)
Fear is a strong and overwhelming emotion that can have negative effects on a child's development and learning if left unaddressed or if reinforced. It is important to encourage parents to take an active role in their child's journey towards overcoming their fears. Helping children how to overcome their fears, especially the fear of being on their own, can help build confidence and resilience in these children, as well as develop healthy coping mechanisms. There are limited visual materials that tackle the topic of overcoming the fear of being on one's own that are available to Filipino parents. In addition to this, a lot of the local visual materials that tackle children's fears fail to emphasize on the importance of parent-involvement and the role of the parent in guiding and comforting their children when dealing with fears. There are also opportunities to improve these materials in order to create and enhanced learning experience that promotes engagement and communication. This study aims to explore the utilization of a multi-sensory storybook kit as a tool for Filipino Parents to build confidence and resilience in their children of ages 6 to 8 who are afraid of being on their own. It aims to emphasize on the importance of parent involvement in the child's process towards coping with fear and to help them recognize approaches which are beneficial for their child's development. It also aims to encourage children to acknowledge their fear and be able to turn to their parents for guidance and support. The goal of this study isn't to completely remove fears from a child, but rather, to guide them towards acknowledging and managing their fears, so they can be brave.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography : leaves 261-265.
Keywords: Fear in children